ANALISIS PROSEDUR PENYIMPANAN ARSIP DALAM MENUNJANG EFEKTIVITAS KERJA PEGAWAI DI KANTOR BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) KOTA PALEMBANG - Laili, Rusdi; Juliati, Reni; Lamingthon, Nifi (STIA SATYA NEGARA PALEMBANG, 2023)
Every organization or company must have archives. Archives are valuable assets, because they have an important r ole as a memory center, an important source of infor mation needed for the running of the organization/company. Work effectiveness is a measure and ability to carry out tasks properly, quickly, precisely and effic iently. A good archive system can help and have an impact on the effectiveness of employees' work and vice versa. This study uses qualitative research methods, data collection techniques with observation, interviews, documentation, and literature studies using Miles and Huberman mode l data analysis techniques, namely by collecting data, data reduction, data presentation, and drawing conclus ions. Based on the results of research and discussion on Archive Storage Procedures in Supporting the Effectiveness of Employees at the General Elections Supervis ory Agency (Bawaslu) of Palembang City, basically it has been running quite well in the archive storage proc edure as well as its effect on the effectiveness of the work of its employees, this can be seen from the achievement of objectives as well as proper completion of tasks. The inhibiting factor is because in the archive storage activities there are still shortcomings, especially in the equipment, facilities, and infrastructure for archive storage, such as file storage cabinets and employees. Keywords: Procedure, Archive Storage, Effectiveness